Makna Denotasi dan Konotasi pada Puisi “Iżā Gāmarta Fī Syarafin Marūmin” Karya Abu Toyyib Al-Mutanabbi - Thaariq, M. Ulfat; Mustari, Mustari (Universitas Al Azhar Indonesia, 2025)
This research aims to analyze the denotation and connotation meanings of poetry